Ascetoaxinus quatsinoensis sp. et gen. nov. (Bivalvia: Thyasiroidea) from Vancouver Island, with notes on Conchocele Gabb, 1866, and Channelaxinus Valentich-Scott & Coan, 2012 - Oliver, P. Graham; Frey, Melissa A. (Zootaxa, 2014)
Ascetoaxinus quatsinoensis sp. et gen. nov. is described from deep waters off the coast of Vancouver Island, British Columbia, Canada. The shell of this species is quite unusual in that the margin of the lunule is distinctly scalloped, a feature not reported previously for the Thyasiroidea. Further investigation led to the discovery of another similarly scalloped shell, represented by the unique type specimen of Cryptodon ovoideus Dall, 1890, herein re-classified as Ascetoaxinus ovoidea (Dall, 1890). Results obtained from scanning electron microscopy reveal additional anatomical differences, including distinct gill structure, that distinguish A. quatsinoensis from other thyasirids examined. Morphological comparisons of this new species to closely related taxa has resulted in a re-evaluation of the genera Conchocele Gabb, 1866, and Channelaxinus Valentich-Scott and Coan, 2012.